Acute effects of exercise on macro- and microvasculature in individuals with type 1 diabetes – a secondary outcome analysis - Saloň, Adam; Schmid-Zalaudek, Karin; Steuber, Bianca; Müller, Alexander; Moser, Othmar; Alnuaimi, Suhaila; Fredriksen, Per Morten; Ngwenchi Nkeh-Chungag, Benedicta; Goswami, Nandu (Frontiers in Endocrinology, 2024)
Background Type 1 diabetes is a chronic autoimmune disease associated with insulin-producing beta cell destruction, declining insulin secretion, and elevated blood glucose. Physical activity improves glycaemic control and cardiovascular health. This study explores acute effects of maximal exhaustion induced by a cardiopulmonary exercise on macro- and microvascular parameters in type 1 diabetes. Methodology Twenty-five participants with type 1 diabetes (14 males, 11 females), aged 41.4 ± 11.87 years, BMI 23.7 ± 3.08, completed a repeated-measure study. Measurements pre-, post-, 30- and 60-minutes post-exhaustion involved a maximal incremental cardio-pulmonary exercise test. Macro- and microvascular parameters were assessed using VICORDER® and retinal blood vessel image analysis. Repeated measures ANOVA in SPSS (Version 27.0) analysed data. Results Post-exercise, heart rate increased (p<.001), and diastolic blood pressure decreased (p=.023). Diabetes duration correlated with pulse wave velocity (r=0.418, p=.047), diastolic blood pressure (r=0.470, p=.023), and central retinal arteriolar equivalent (r=0.492, p=.023). Conclusion In type 1 diabetes, cardiopulmonary exercise-induced exhaustion elevates heart rate and reduces diastolic blood pressure. Future research should explore extended, rigorous physical activity protocols for greater cardiovascular risk reduction.